Is the European Crop Protection Industry Threatened by the Drive Towards Transparency?. (1st April 2019) - Blake, Robin
From 23–26 May 2019 European Union (EU) citizens will be given the opportunity to select who will represent them in the European Parliament for the next five years. They will help determine how Europe will act to address public concerns such as the state of the economy, jobs, security, migration, climate change and food security. Given that the term of the current incumbents is almost up it seems appropriate to review their time in charge to determine whether science and science-based rationale are still central to EU decision-making. From a crop protection industry perspective, the period 2014 to 2019 will likely be remembered for the debacle surrounding the renewal of glyphosate, concerns over data transparency and independence, and attempts to improve the Plant Protection Product (PPP) authorisation process.